Caribbean island movements : Culebra's trans-insularities - Cubero, Carlo A. (Rethinking the island, 2017)
An ethnographic account of how the islanders of the Caribbean island of Culebra reproduce a sense of unique insular identity, while engaged in continuous practices of regional and global movements.